Dignity, Community and Albinism in Malawi - Nyirenda, Vitumbiko (Bangladesh Journal of Bioethics, 2019)
Thaddeus Metz, “African conceptions of human dignity” (2012), presents an African conception of dignity that he relates to human rights. In this paper, while ignoring Metz’s discussion on human rights, I specifically look at how this conception can be applied to one of the problematic moral issues, killing of persons with albinism. That is, how Metz’s view would account for exclusion and wrongness of killing of persons with albinism. I argue that the killing of persons with albinism is acting in violation of their dignity. This comes from the view that persons with Albinism are human beings with a dignity, and therefore ought not to be killed. I offer a discussion on how dignity as capacity for community based on shared identity and good-will is not reflected in the way persons with albinism are treated in Malawi.